Enhanced Ferromagnetism in Nanoscale GaN:Mn Wires Grown on GaN Ridges - Cheng, Ji (Materials (Basel), 2017)
The problem of weak magnetism has hindered the application of magnetic semiconductors since their invention, and on the other hand, the magnetic mechanism of GaN-based magnetic semiconductors has been the focus of long-standing debate. In this work, nanoscale GaN:Mn wires were grown on the top of GaN ridges by metalorganic chemical vapor deposition (MOCVD), and the superconducting quantum interference device (SQUID) magnetometer shows that its ferromagnetism is greatly enhanced. Secondary ion mass spectrometry (SIMS) and energy dispersive spectroscopy (EDS) reveal an obvious increase of Mn composition in the nanowire part, and transmission electron microscopy (TEM) and EDS mapping results further indicate the correlation between the abundant stacking faults (SFs) and high Mn doping. When further combined with the micro-Raman results, the magnetism in GaN:Mn might be related not only to Mn concentration, but also to some kinds of built-in defects introduced together with the Mn doping or the SFs.